EFEKTIVITAS MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENGANALISIS UNSUR-UNSUR INTRINSIK DAN EKSTRINSIK DRAMA AYAHKU PULANG DI KELAS VIII SMPN 01 BURNEH - Faizol, Ahmad; Sakrim, Sakrim (Jurnal Sastra Aksara, 2019)
This research was motivated by the low of students’ desire to learn. Student learning difficulties due to various problems that cause students to feel bored. The purpose of this research were to describe (1) effectiveness for students, (2) students’ response, (3) students’ learning outcomes before using audio visual media, (4) students’ learning outcomes after using audio visual media. For this reason, the teacher’s task in the learning process is to create more active, productive and effective learning atmosphere. Thus, learning in the classroom is getting easier according to the expected goals. This research used media to improve students’ learning outcomes by using audio visual learning media in drama material. This research approach used descriptive quantitative to analyze the research data. The results of this research, it can be concluded that during the learning process using audio visual learning media, it could be said to be effective because it reached 2 categories: the results of students’ response questionnaires with 79% results in the category of students feel effective. And that answers the response of students 84% ​​results that have been percentage very well, students’ learning outcomes before using audio visual media with an average value of 50, students’ learning outcomes after using audio visual media was very good with an average value of 82. The existence of media in learning could add new knowledge to students so that it increased the interest to create and write intrinsic and extrinsic elements in drama material.